Efisiensi Tata Letak Gudang Penyimpanan Barang Jadi dengan Metode Class Based Storage di PT. XYZ - Rahayu, Siti; Santoso, Eko (Universitas Mercu Buana, 2023)
One of the problems in the layout of finished goods warehouse storage is the inaccurate and ineffective placement of goods. At the PT XYZ warehouse, the storage process at the finished goods warehouse is still done manually and the process of placing goods on shelves is still random, while the goods stored in the warehouse have various types of product items with different sizes. This problem results in delays in handling goods in the warehouse, and reduces productivity when placing and picking up goods. To produce the right storage layout during the storage process and how to place goods in an orderly manner, namely by using the class based storage method to speed up the process of moving goods in the warehouse and to facilitate management and access to relevant information when searching for goods. The results of changes to the layout of finished goods storage in the finished goods warehouse based on class ABC on the Class Based method can reduce efficiency by 22.04% for product search while for placement of finished products by 18.04%.